Non-invasive evaluation of esophageal varices in patients with liver cirrhosis using low-dose splenic perfusion CT. Issue 152 (July 2022) - Yan, Cheng; Han, Xinjun; Liang, Xiaohong; Jia, Jidong; Xu, Youqing; Zhao, Liqin
Highlights: Splenic perfusion CT parameters BV and BF can reflect the severity of EV. PS, V-S and BV-S in cirrhotic patients were higher than those in non-cirrhotic patients. Low-dose splenic perfusion CT could be performed using 256-row DECT scanner. Low-dose splenic perfusion CT could be used to predict EVB noninvasively. Abstract: Purpose: To assess the value of splenic hemodynamic parameters measured using low-dose perfusion CT in the noninvasive evaluation of esophageal varices (EV) in patients with liver cirrhosis. Methods: We retrospectively studied 43 cirrhotic patients with EV, which were divided into mild (EV1), moderate (EV2) and severe (EV3) groups. 14 patients with normal liver function and no EV were selected as the control group. All patients underwent low-dose splenic perfusion CT and radiation dose were recorded. Spleen perfusion parameters, including blood volume (BV), blood flow (BF) and permeability surface (PS), were obtained. The volume of the spleen (V-S) was measured. The total blood volume of the spleen (BV-S) was obtained using the product of V-S and BV. The measurement differences among the four groups were analyzed using ANOVA with Welch correction. Least Significant Difference (LSD) was used for the multiple comparison. P < 0.05 was considered statistically significant. Results: There were statistically significant differences in BV, BF, PS, V-S, and BV-S among different groups (p < 0.05). PS, V-S, and BV-S were higher, and BV and BF were lower in the study groups than those in the control group. There was a statistically significant difference between EV2 and EV1 groups, and EV2 and EV3 groups in BV and BF. The average dose-length product (DLP) was 1286.41 ± 261.15 mGy*cm, and the effective radiation dose（Deff ）was 19.30 ± 3.92 mSv. Conclusion: The splenic perfusion parameters obtained in the low-dose splenic perfusion CT could be used to noninvasively evaluate the degrees of EV in cirrhotic patients.